Macroeconomic Determinants of Stock Market Development: A Systematic Literature Review - Akash Chaurasia; Prashant Debnath; Mohammed Juraij N (Jurnal Multidisiplin Madani, 2023)
The objective of this study is to examine the various macroeconomic factors that influence the growth of the stock market, as well as to explore the techniques employed to establish a correlation between them. For this research, literature was sourced from databases such as Ebsco host, Web of Science, and JSTOR using the search terms "Macroeconomic determinants" and "Stock market". The data obtained was then analyzed using the PRISMA statement and presented in the report accordingly.The study revealed that economic growth has a positive effect on the growth of the stock market, while an increase in the inflation rate has a negative impact. The impact of trade openness, foreign investment, exchange rate, interest rate, and banking sector development was found to be mixed. The correlation between these macroeconomic determinants and stock market development was established by utilizing econometric techniques, including GARCH and ARCH models. This research aims to provide an understanding of the relationship between macroeconomic factors and the development of the stock market, as well as the impact of these factors. However, more in-depth exploration of this topic is needed, including the examination of additional databases and analysis on a country and sectoral level. This research will assist scholars and educators within the fields of economics and finance to gain insight into the macroeconomic factors that influence the growth of the stock market. As far as the researcher is aware, no systematic review using the PRISMA framework has been conducted on the relationship between "macroeconomic determinants" and "stock market development